1999
DOI: 10.1128/jcm.37.7.2378-2380.1999
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae in a Free-Ranging Giant Barred Frog ( Mixophyes iteratus ) from Australia

Abstract: The koala biovar of Chlamydia pneumoniae was identified in lung tissue from a sick, free-ranging giant barred frog (Mixophyes iteratus) by using electron microscopy, C. pneumoniae-specific fluorescent-antibody staining, cell culture, and sequencing of the ompA, ompB and 16S rRNA genes. This is the first report of a chlamydial strain infecting both a homeotherm and a poikilotherm and only the fourth host (in addition to humans, koalas, and horses) to be naturally infected with this species of Chlamydia. The fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Moreover, unknown Chlamydia or C. psittaci infections have been reported in captive amphibians, causing moderate to high mortality rates in various species, including African clawed frogs (Xenopus laevis) in the United States (46)(47)(48). C. pneumoniae infection has been also reported in the free-ranging giant barred frog (Mixophyes iteratus) in Australia (24), and in free-ranging frogs in Switzerland (26). Taken together with our results showing a high prevalence of C. pneumoniae DNA in soil (20%) and no correlation between the prevalence of C. pneumoniae DNA, and Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, unknown Chlamydia or C. psittaci infections have been reported in captive amphibians, causing moderate to high mortality rates in various species, including African clawed frogs (Xenopus laevis) in the United States (46)(47)(48). C. pneumoniae infection has been also reported in the free-ranging giant barred frog (Mixophyes iteratus) in Australia (24), and in free-ranging frogs in Switzerland (26). Taken together with our results showing a high prevalence of C. pneumoniae DNA in soil (20%) and no correlation between the prevalence of C. pneumoniae DNA, and Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the route of infection from C. pneumoniae in the soil environment to humans is not easy to explain. C. pneumoniae infection has occurred in amphibians, koalas and horses; nevertheless, direct human infection from such species is unlikely (23,24,(27)(28)(29)(45)(46)(47)(48). Moreover, Bourke et al have reported a high prevalence of antibodies to C. pneumoniae in farmers in the United Kingdom (52), strongly implying that transmission may occur via a contagious source of C. pneumoniae in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berger and colleagues were the first to identify Chlamydophila pneumoniae by PCR in the lung of a Giant Barred Frog with chronic mononuclear pneumonia. 4 Reed et al reported an epizootic in a breeding colony of Xenopus tropicalis due to Cp pneumoniae in combination with the chytrid fungus B dendrobatidis. 23 In 2001, Hotzel et al showed by comparison of all currently known isolates of Cp pneumoniae that the isolate they found in African frogs (Cryptohylax gresshoffi) was closest to the koala biovar.…”
Section: Introductionmentioning
confidence: 99%
“…C. pneumoniae is unique within the Chlamydiaceae family as this organism is thought to have been relatively recently acquired from animal sources (Myers et al, 2009). C. pneumoniae has been identified in numerous animals including koalas, snakes, horses and other mammals (Berger et al, 1999;Bodetti and Timms, 2000;Bodetti et al, 2002a,b;. Recently, comparative genomics identified that the koala respiratory isolate, C. pneumoniae LPCoLN, is potentially ancestral to some human C. pneumoniae isolates (Myers et al, 2009;Mitchell et al, 2010a,b).…”
Section: Introductionmentioning
confidence: 99%